Composition, hard tissue repair composition, hard tissue repair kit, and method for manufacturing composition

A (meth)acrylate polymer and contrast agent composition with controlled aggregation ensures high compressive strength and contrast in hard tissue repair, addressing the strength reduction issue in existing compositions.

JP2024176313AInactive Publication Date: 2024-12-19MITSUI CHEMICALS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023094770
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-08
Publication Date
2024-12-19
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Hard tissue repair compositions often suffer from reduced compressive strength due to the addition of contrast agents, which can lead to insufficient fixation and mobility issues when used as bone cement for artificial joints.

Method used

A composition comprising a (meth)acrylate polymer and a contrast agent with aggregate major axes less than 1.0 mm, preferably using barium sulfate or zirconium oxide, and a specific mass ratio of 1:0.003 to 1:1.8, along with optional antibacterial particles, to ensure uniform dispersion and maintain compressive strength.

Benefits of technology

The solution achieves a cured product with sufficient compressive strength and contrast properties, reducing aggregation and maintaining mechanical integrity for bone repair applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176313000001
    Figure 2024176313000001
  • Figure 2024176313000002
    Figure 2024176313000002
  • Figure 2024176313000003
    Figure 2024176313000003
Patent Text Reader

Abstract

To provide a composition capable of providing a cured body of a hard tissue repair composition having sufficient and appropriate compressive strength while having radiopacity.SOLUTION: A composition includes a (meth)acrylate polymer (A) and a contrast medium (B). A long diameter of an aggregate of the contrast medium (B) in the composition is less than 1.0 mm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition, a composition for hard tissue repair, a kit for hard tissue repair, and a method for producing the composition. [Background technology]

[0002] 2. Description of the Related Art Various compositions for repairing hard tissues have been investigated so far as bone cements for fixing hard tissues such as bone and cartilage to artificial joints, bone fillers for use in treating osteoporosis, and artificial bone materials.

[0003] For example, Patent Document 1 discloses a composition for hard tissue repair that contains a (meth)acrylate monomer (A), a (meth)acrylate polymer (B), a polymerization initiator (D) and a contrast agent (X). This composition generates little heat when cured and has excellent operability. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2019 / 181477 Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, a composition for hard tissue repair usually contains a monomer and a polymer as a base material, and a contrast agent for providing contrast ability. On the other hand, the addition of the contrast agent may reduce the compressive strength of the cured body.

[0006] For example, when a hardened composition for hard tissue repair having a low compressive strength is used as a bone cement for fixing an artificial joint, the fixation may be insufficient, resulting in problems such as difficulty in walking, etc. Therefore, it is desired that the hardened composition for hard tissue repair has a sufficient and appropriate compressive strength even if it contains a contrast agent.

[0007] The object of the present invention is to provide a composition capable of providing a hardened body of a hard tissue repair composition having contrast properties while having sufficient and appropriate compressive strength, a hard tissue repair composition obtained from said composition, a hard tissue repair kit, and a method for producing the composition. [Means for solving the problem]

[0008] [1] A composition comprising a (meth)acrylate polymer (A) and a contrast agent (B), wherein the major axis of aggregates of the contrast agent (B) in the composition is less than 1.0 mm. [2] The composition according to [1], wherein the contrast agent (B) comprises barium sulfate or zirconium oxide. [3] The composition according to [1] or [2], wherein the content ratio of the (meth)acrylate polymer (A) to the contrast agent (B) is (A):(B)=1:0.003 to 1:1.8 (mass ratio). [4] The composition according to any one of [1] to [3], wherein the content of the (meth)acrylate polymer (A) is 33 to 99.8 mass % based on the total amount of the composition. [5] The composition according to any one of [1] to [4], wherein the content of the contrast agent (B) is 0.1 to 65 mass % based on the total amount of the composition. [6] The composition according to any one of [1] to [5], wherein the contrast agent (B) has a volume average particle size of 5.0 μm or less. [7] The composition described in any of [1] to [6], further comprising antibacterial particles (Z). [8] The composition described in any of [1] to [7], wherein the content of the antibacterial particles (Z) is 0.1 to 20 mass% relative to the total amount of the composition. [9] A composition for hard tissue repair, comprising the composition according to any one of [1] to [8], a (meth)acrylate monomer (C), and a polymerization initiator (D).

[10] The composition for hard tissue repair described in [9], which is used for bone repair.

[11] A kit for hard tissue repair, comprising a member in which the composition according to any one of [1] to [8], a composition containing a (meth)acrylate monomer (C), and a composition containing a polymerization initiator (D) are contained separately.

[12] A kit for hard tissue repair, comprising a member containing, in a separated form, a first composition containing one of a (meth)acrylate monomer (C) and a polymerization initiator (D) and the composition described in [1] to [8], and a second composition containing the other of the (meth)acrylate monomer (C) and the polymerization initiator (D).

[13] A method for producing a composition, comprising the step of mixing a (meth)acrylate polymer (A) and a contrast agent (B) by stirring in a mixer equipped with a stirring blade, in which the (meth)acrylate polymer (A) and the contrast agent (B) are mixed in a ratio of (A):(B) = 1:0.003 to 1:1.8 (mass ratio) and the tip blade speed of the stirring blade is 5 to 30.0 m / s.

[14] The method for producing the composition described in

[13] , wherein the contrast agent (B) contains barium sulfate or zirconium oxide.

[15] The method for producing a composition according to

[13] or

[14] , wherein the volume average particle diameter of the contrast agent (B) is 5.0 μm or less.

[16] A method for producing a composition according to any one of

[13] to

[15] , further comprising antibacterial particles (Z). Effect of the Invention

[0009] According to the present invention, there are provided a composition capable of providing a hardened body of a hard tissue repair composition having contrast properties while having sufficient and appropriate compressive strength, a hard tissue repair composition obtained from said composition, a hard tissue repair kit, and a method for producing the composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] A composition according to one embodiment of the present invention will be described below. In this specification, the term "to" means a numerical range including a lower limit and an upper limit, which are the endpoints.

[0011] 1. Composition A composition according to one embodiment of the present invention contains a (meth)acrylate polymer (A) and a contrast agent (B). The composition is one of the materials for obtaining a composition for hard tissue repair, and is preferably a powder composition used as a bone cement powder. Hereinafter, the composition is referred to as the "composition" or "the composition" in the present specification.

[0012] In general, the contrast agent (B) has a tendency to aggregate, and is therefore difficult to disperse uniformly in the composition, which can result in a decrease in compressive strength of the hardened body of the resulting composition for hard tissue repair.

[0013] In response to this, the present inventors conducted extensive research and found that the decrease in compressive strength of the cured body can be reduced by reducing the aggregation of the contrast agent (B) in a composition containing a (meth)acrylate polymer (A) and the contrast agent (B), specifically, by making the major axis of the aggregates less than 1.0 mm.

[0014] Specifically, when the major axis of the aggregate of contrast agent (B) in the composition is less than 1.0 mm, the contrast agent (B) can be uniformly dispersed in the obtained hardened body of the composition for hard tissue repair. This not only makes the contrast property uniform, but also reduces the decrease in the compressive strength of the hardened body. From the same viewpoint, the major axis of the aggregate of contrast agent (B) is preferably 0.05 to 0.8 mm, more preferably 0.1 to 0.4 mm.

[0015] The major axis of the aggregate of the contrast agent (B) can be measured by the following procedure. First, the composition is spread on a polyethylene plate in a uniform layer of 2 mm thickness (circular shape with a diameter of φ=10 mm) and photographed with an X-ray fluoroscopy device FLEX-M863 (manufactured by Beam Sense Co., Ltd.) The tube voltage of the X-ray fluoroscopy device is 70 kV, the tube current is 100 μA, the photographing time is 1000 ms, and the number of additions is 3. In the obtained image, the major axis of any five highly X-ray-opaque parts (aggregates of contrast agent (B)) in the measurement region (circular with a diameter of φ=10 mm) is measured by image analysis. The longest major axis value among these is regarded as the major axis of the aggregate.

[0016] The major axis of the aggregates of the contrast agent (B) can be adjusted mainly by the content ratio of the (meth)acrylate polymer (A) and the contrast agent (B) and the mixing conditions (rotation speed and tip stirring blade speed). By increasing the content ratio of the (meth)acrylate polymer (A) and the contrast agent (B) and appropriately easing the mixing conditions (stirring blade speed and rotation speed of the mixer), the major axis of the aggregates of the contrast agent (B) can be made small. Each component will be specifically described below.

[0017] 1-1. (Meth)acrylate polymer (A) The (meth)acrylate polymer (A) is a polymer containing a structural unit derived from a (meth)acrylate monomer. In this specification, (meth)acrylate is a general term for acrylate and methacrylate.

[0018] The (meth)acrylate monomer may be the same as the (meth)acrylate monomer (C) described later. The (meth)acrylate monomer may be, for example, an alkyl (meth)acrylate such as methyl (meth)acrylate; a hydroxyalkyl (meth)acrylate ester such as 2-hydroxyethyl (meth)acrylate; or a polyethylene glycol mono(meth)acrylate such as triethylene glycol monomethyl ether (meth)acrylate. The (meth)acrylate monomer may contain the same type of (meth)acrylate monomer as the (meth)acrylate monomer (C) described later.

[0019] Examples of the (meth)acrylate polymer (A) include non-crosslinked polymers such as polymethyl(meth)acrylate, polyethyl(meth)acrylate, methyl(meth)acrylate-ethyl(meth)acrylate copolymer, methyl(meth)acrylate-butyl(meth)acrylate copolymer, and methyl(meth)acrylate-styrene copolymer; crosslinked polymers such as methyl(meth)acrylate-ethylene glycol di(meth)acrylate copolymer, methyl(meth)acrylate-triethylene glycol di(meth)acrylate copolymer, and copolymer of methyl(meth)acrylate and butadiene monomer, and polymers partially forming calcium salts. In addition, the polymer may be an organic-inorganic composite in which a metal oxide or a metal salt is coated with a non-crosslinked polymer or a crosslinked polymer.

[0020] Among these, the (meth)acrylate polymer (A) preferably contains a structural unit derived from methyl methacrylate. The content of the structural unit derived from methyl methacrylate in the (meth)acrylate polymer (A) is preferably 35% by mass or more, more preferably 65% ​​by mass or more, based on the total structural units of the polymer (A). An example of the (meth)acrylate polymer (A) containing a structural unit derived from methyl methacrylate is polymethyl methacrylate (PMMA). The polymer (A) may further contain a structural unit derived from another copolymerization monomer other than methyl methacrylate. Examples of the other copolymerization monomer include (meth)acrylic acid alkyl esters other than methyl (meth)acrylate, styrenes, (meth)acrylic acid hydroxyalkyl esters, polyethylene glycol mono(meth)acrylate, and the like.

[0021] The weight-average molecular weight of the (meth)acrylate polymer (A) is preferably 50,000 to 5,000,000, more preferably 75,000 to 2,000,000, even more preferably 75,000 to 880,000, and particularly preferably 100,000 to 400,000. When the weight-average molecular weight is equal to or greater than the lower limit, the compressive strength of the hardened body of the hard tissue repair composition can be further increased. When the weight-average molecular weight is equal to or less than the upper limit, the operability of applying and / or filling the hard tissue repair composition to the affected area immediately after preparation of the hard tissue repair composition (during curing) can be further improved, and properties such as penetration into hard tissue can be further improved.

[0022] The weight average molecular weight can be measured by gel permeation chromatography (GPC) in terms of standard polystyrene. Specifically, the (meth)acrylate polymer (A) is dissolved in reagent grade tetrahydrofuran (manufactured by Wako Pure Chemical Industries, Ltd.), and the solution is filtered through a hydrophobic 0.45 μm polytetrafluoroethylene filter. The filtered solution is used as a sample, and the weight average molecular weight (Mw) of the (meth)acrylate polymer (A) is measured in terms of standard polystyrene using a high performance liquid chromatography (Shimadzu Corporation, LC-10AD), a separation column (PLgel (10 μm) MIXED-B × 2), and a detector (Shodex Corporation, RI-101).

[0023] The form of the (meth)acrylate polymer (A) is not particularly limited, but is preferably particulate. The shape of the particles of the (meth)acrylate polymer (A) may be spherical or irregular.

[0024] Volume average particle diameter D of (meth)acrylate polymer (A) 50 From the viewpoint of adjusting the pot life (setting time) of the hard tissue repair composition to an appropriate length, the volume average particle diameter D of the (meth)acrylate polymer (A) is preferably 7 to 120 μm, more preferably 10 to 118 μm, and further preferably 15 to 77 μm. 50 means the volume average particle size of the primary particles of the (meth)acrylate polymer (A).

[0025] Volume average particle size D 50 can be measured by the following procedure. Using special reagent grade methanol (solvent refractive index 1.33) (manufactured by Wako Pure Chemical Industries, Ltd.) as a dispersion solvent, particles of the (meth)acrylate polymer (A) are dispersed for 5 minutes (output 25 W) using the built-in ultrasonic homogenizer of the device. The volume average particle size of the (meth)acrylate polymer (A) in the obtained dispersion is measured using a Microtrac MT3300EXII (a particle size distribution analyzer manufactured by Microtrac Corp.) at a concentration condition within an appropriate range of the device loading index and a circulation speed of 50% (65 mL / sec at 100%).

[0026] The composition may contain one type of (meth)acrylate polymer (A) or may contain two or more types of (meth)acrylate polymers. For example, the composition may contain two or more types of (meth)acrylate polymers having different volume average particle sizes, or may contain two or more types of (meth)acrylate polymers having different particle shapes.

[0027] For example, the composition may contain a spherical (meth)acrylate polymer (A1) and an amorphous (meth)acrylate polymer (A2). The spherical particles have a relatively small specific surface area, and the amorphous particles have a relatively large specific surface area, so they can be distinguished by their specific surface areas. In this embodiment, the specific surface area of ​​the spherical (meth)acrylate polymer (A1) is preferably 0.05 to 1.2 m 2 / g, more preferably 0.1 to 0.7m 2 The specific surface area of ​​the amorphous (meth)acrylate polymer (A2) is preferably 1.5 to 4.5 m 2 / g, more preferably 2.5 to 3.5 m 2 / g.

[0028] The specific surface area can be measured by performing vacuum degassing at room temperature as a pretreatment, and then using a BELSORP-mini (manufactured by MicrotrackBell) apparatus, using a nitrogen gas adsorption method at liquid nitrogen temperature.

[0029] The weight average molecular weight of the spherical (meth)acrylate polymer (A1) can be preferably 10,000 to 5,000,000, more preferably 50,000 to 1,540,000, and even more preferably 100,000 to 500,000. The volume average particle size can be preferably 1.0 to 77 μm, more preferably 3.5 to 58 μm, and particularly preferably 17.5 to 50 μm.

[0030] The weight average molecular weight of the amorphous (meth)acrylate polymer (A2) can be preferably 150,000 to 5,000,000, more preferably 200,000 to 1,150,000, and even more preferably 240,000 to 670,000. The volume average particle size can be preferably 0.3 to 60 μm, more preferably 7.5 to 50 μm, and even more preferably 15.7 to 40 μm.

[0031] When the (meth)acrylate polymers (A1) and (A2) are used in combination, the content of the (meth)acrylate polymer (A1) can be preferably 50.5 to 95 parts by mass, more preferably 65 to 90 parts by mass, and the content of the (meth)acrylate polymer (A2) can be preferably 5 to 49.5 parts by mass, more preferably 10 to 35 parts by mass, per 100 parts by mass of the (meth)acrylate polymer (A).

[0032] The content of the (meth)acrylate polymer (A) is not particularly limited, but is preferably 33 to 99.8% by mass relative to the total amount of the composition. When the content of the (meth)acrylate polymer (A) is 33% by mass or more, the content of the contrast agent (B) is reduced, so that the aggregation of the contrast agent (B) can be reduced, and the decrease in the compressive strength of the hardened body of the hard tissue repair composition can be reduced. When the content of the (meth)acrylate polymer (A) is 99.8% by mass or less, the content of the contrast agent (B) is greater than or equal to a predetermined amount, so that the contrast property can be improved. From the same viewpoint, the content of the (meth)acrylate polymer (A) is more preferably 49 to 92.5% by mass.

[0033] From the same viewpoint as above, the content of the (meth)acrylate polymer (A) is, for example, preferably 40 to 80 parts by mass, and more preferably 45 to 75 parts by mass, per 100 parts by mass of the total of the components (A), (C) and (D).

[0034] 1-2. Contrast media (B) The type of contrast agent (B) is not particularly limited, and examples thereof include barium sulfate, zirconium oxide, bismuth carbonate, calcium tungstate, ytterbium, and iodine compounds. Among them, barium sulfate and / or zirconium oxide are preferred from the viewpoint of their excellent contrast properties when used in a composition for repairing hard tissue, since they have a proven track record of use in hard tissue applications, particularly as bone cement.

[0035] Volume average particle size D of contrast agent (B) 50 is not particularly limited, but is preferably 25.1 μm or less, more preferably 21.5 μm or less, further preferably 6.0 μm or less, and particularly preferably 5.0 μm or less. 50 The lower limit of the volume average particle diameter D of the contrast agent (B) is not particularly limited, but is preferably 0.01 μm, more preferably 0.02 μm, further preferably 0.1 μm, and particularly preferably 0.9 μm. 50When the volume average particle diameter D of the contrast agent (B) is equal to or larger than the lower limit, aggregation of the contrast agent (B) is less likely to occur, and as a result, the decrease in compressive strength of the hardened body of the composition for hard tissue repair can be reduced. 50 When the volume average particle diameter D of the contrast agent (B) is equal to or less than the upper limit, the dispersion of antibacterial particles (Z) contained in the composition is further promoted, and as a result, excellent and / or stable antibacterial performance can be imparted to the hardened body of the composition for hard tissue repair. 50 means the volume average particle size of the primary particles of the contrast agent (B).

[0036] The content of the contrast agent (B) is not particularly limited, but is preferably 0.1 to 65% by mass relative to the total amount of the composition. When the content of the contrast agent (B) is 0.1% by mass or more, the contrast property of the hardened body of the hard tissue repair composition can be further improved. When the content of the contrast agent (B) is 65% by mass or less, the aggregation of the contrast agent (B) can be further reduced, and the decrease in compressive strength of the hardened body can be further reduced. From the same viewpoint, the content of the contrast agent (B) is more preferably 7.5 to 51% by mass, and particularly preferably 9% by mass to 32% by mass.

[0037] The content ratio of the (meth)acrylate polymer (A) and the contrast agent (B) contained in the above composition is not particularly limited, but is preferably (A):(B)=1:0.003 to 1:1.8 (mass ratio). When the content ratio of (B) is equal to or greater than the lower limit, the contrast property of the hardened body of the hard tissue repair composition can be further improved. When the content ratio of (B) is equal to or less than the upper limit, the aggregation of the contrast agent (B) can be further reduced, so that the major axis of the aggregate of the contrast agent (B) in the composition can be further reduced. This can further reduce the decrease in the compressive strength of the hardened body of the hard tissue repair composition. From the same viewpoint, it is more preferable that (A):(B)=1:0.01 to 1:1 (mass ratio), and particularly preferably 1:0.05 to 1:1 (mass ratio).

[0038] 1-3.Other ingredients The composition may further contain other components as necessary. Examples of the other components include antibacterial agent particles, inorganic fillers, colorants, etc.

[0039] 1-3-1. Antibacterial particles (Z) The composition may contain antibacterial particles (Z) in addition to the (meth)acrylate polymer (A) and the contrast agent (B). Specific examples of antibacterial agents include antibiotics, elemental iodine, solid polyvinylpyrrolidone iodine, polyvinylpyrrolidone iodine; tribromophenol, trichlorophenol, tetrachlorophenol, nitrophenol, 3-methyl-4-chloro-phenol, 3,5-dimethyl-4-chlorophenol, phenoxyethanol, dichlorophene, o-phenylphenol, m-phenylphenol, p-phenylphenol, 2-benzyl-4-chlorophenol, 2,4-dichloro-3,5-dimethylphenol, 4-chlorothymol, chlorphene, triclosan, fenticrol, phenol, 2-methylphenol, 3,4-dichloro-3,5-dimethylphenol, 4-chlorothymol, chlorphene, triclosan, fenticrol, phenol, 2-methylphenol, 3,5-dimethylphenol, 3,6-dichloro-3,5-dimethylphenol, 3,7-dichloro-3,5-dimethylphenol, 3,8-dichloro-3,5-dimethylphenol, 3,9-dichloro-3,5-dimethylphenol, 3,8-dichloro-3,5-dimethylphenol, 3,9-dichloro-3,5-dimethylphenol, 3,10-dichloro- ... phenolic compounds such as 1-methylphenol, 4-methylphenol, 4-ethylphenol, 2,4-dimethylphenol, 2,5-dimethylphenol, 3,4-dimethylphenol, 2,6-dimethylphenol, 4-n-propylphenol, 4-n-butylphenol, 4-n-amylphenol, 4-tert-amylphenol, 4-n-hexylphenol, 4-n-heptylphenol, monoalkylhalophenols, polyalkylhalophenols, aromatic halophenols, and their ammonium salts, alkali metal salts, and alkaline earth metal salts; silver nitrate, hexachlorophene, and merbromin. Among these, antibiotics are preferred.

[0040] An antibiotic is a substance produced by a microorganism or chemically synthesized that inhibits the growth of other microorganisms. Furthermore, this definition of antibiotics also includes substances that have been chemically transformed from substances produced by a microorganism or chemically synthesized.

[0041] Specific examples of antibiotics include gentamicin, gentamicin sulfate, tobramycin, tobramycin sulfate, amikacin, amikacin sulfate, dibekacin, dibekacin sulfate, vancomycin, vancomycin hydrochloride, daptomycin, arbekacin, arbekacin sulfate, fosfomycin, cefazolin, cefazolin sodium salt, minocycline, clindamycin, colistin, linezolid, tetracycline hydrochloride, tetracycline hydrate, oxytetracycline, and erythromycin. Among them, it is preferable to include one or more antibiotics selected from the group consisting of gentamicin, tobramycin, amikacin, dibekacin, vancomycin, daptomycin, and pharmacologically acceptable salts thereof.

[0042] When daptomycin and a pharmacologically acceptable salt of daptomycin are used as the antibacterial particles (Z), it is preferable that the composition further contains, among the inorganic fillers described below, a filler having a sustained calcium release property in particular. The daptomycin derivative bound to calcium element or ion contained in the hard tissue repair composition applied to and / or filled in the affected area penetrates and binds to the bacterial cell membrane, causing depolarization in the cell membrane and loss of membrane potential, thereby causing the death of the bacteria, which tends to improve the antibacterial property. These sustained calcium release fillers can be used alone or in combination of two or more kinds.

[0043] The volume average particle size of the antimicrobial particles (Z) is preferably less than 250 μm, more preferably 1.0 to 200 μm, and more preferably 2.5 to 150 μm.

[0044] The content of the antibacterial particles (Z) is not particularly limited, but is preferably 0.1 to 20% by mass relative to the total amount of the composition. When the content of the antibacterial particles (Z) is 0.1% by mass or more, the antibacterial properties of the composition for hard tissue repair tend to improve. When the content is 20% by mass or less, the aggregation of the contrast agent (B) can be further reduced, and the decrease in compressive strength of the hardened body can be further reduced. From the same viewpoint, the content of the antibacterial particles (Z) is more preferably 1 to 15% by mass.

[0045] 1-3-2. Inorganic fillers The composition may contain an inorganic filler (excluding the above-mentioned contrast agent) in addition to the (meth)acrylate polymer (A) and the contrast agent (B). A hard tissue repair composition prepared from a composition containing an inorganic filler tends to have the effects of, for example, clarifying the visual distinction from the surrounding bone tissue, improving adhesion, enhancing properties such as compressive strength, and reducing the harmfulness to the surrounding bone tissue by capturing active radical species.

[0046] Examples of inorganic fillers include metal oxide powders such as bismuth oxide, titanium oxide, zinc oxide, and aluminum oxide particles; metal salt powders such as zirconium phosphate; glass fillers such as silica glass, aluminum-containing glass, barium-containing glass, strontium-containing glass, and zirconium silicate glass; fillers with sustained silver release properties, fillers with sustained calcium release properties, and fillers with sustained fluorine release properties. From the viewpoint of forming a strong bond between the inorganic filler and the (meth)acrylate monomer (C) contained in the hard tissue repair composition during curing, it is preferable to use an inorganic filler that has been subjected to a surface treatment such as silane treatment or polymer coating. These inorganic fillers can be used alone or in combination of two or more kinds.

[0047] Examples of fillers having calcium sustained release properties include calcium dihydrogen phosphate, calcium dihydrogen phosphate monohydrate, calcium hydrogen phosphate, calcium hydrogen phosphate dihydrate, tricalcium phosphate, octacalcium phosphate, hydroxyapatite, fluoroapatite, chlorapatite, carbonate-containing hydroxyapatite, calcium gluconate, calcium glucuronate, calcium lactate, calcium acetate, calcium sorbate, calcium sulfate dihydrate, calcium sulfate hemihydrate, α-tricalcium phosphate, and β-tricalcium phosphate. These fillers having calcium sustained release properties can be used alone or in combination of two or more.

[0048] 1-3-3. Coloring agents The composition may further contain a colorant in addition to the (meth)acrylate polymer (A) and the contrast agent (B). Examples of the colorant include Red No. 2 and its aluminum lake, Red No. 3 and its aluminum lake, Red No. 102 and its aluminum lake, Red No. 104 (1) and its aluminum lake or barium lake, Red No. 105 (1) and its aluminum lake, Red No. 106 and its aluminum lake, Yellow No. 4 and its aluminum lake or barium lake or zirconium lake, Yellow No. 5 and its aluminum lake or barium lake or zirconium lake, Green No. 3 and its aluminum lake, and the like. Aluminum Lake, Blue No. 1 and its Aluminum Lake, or Barium Lake, or Zirconium Lake, Blue No. 2 and its Aluminum Lake, Red 201, Red 202, Red 203, Red 204, Red 205, Red 206, Red 207, Red 208, Red 213, Red 214, Red 215, Red 218, Red 219, Red 220, Red 221, Red 223, Red 225, Red 226, Red 227 and its Aluminum Lake, Red 228, Red 230 (1) and its Aluminum Lake Umium Lake, Red 230 (2) and its Aluminum Lake, Red 231 and its Aluminum Lake, Red 232 and its Aluminum Lake, Orange 201, Orange 203, Orange 204, Orange 205 and its Aluminum Lake, or Barium Lake, or Zirconium Lake, Orange 206, Orange 207 and its Aluminum Lake, Yellow 201, Yellow 202 (1) and its Aluminum Lake, Yellow 202 (2) and its Aluminum Lake, Yellow 20 No. 3 and its aluminum lake, or barium lake, or zirconium lake, Yellow 204, Yellow 205, Green 201 and its aluminum lake, Green 202, Green 204 and its aluminum lake, Green 205 and its aluminum lake, or zirconium lake, Blue 201, Blue 202 and its barium lake, Blue 203, Blue 204, Blue 205 and its aluminum lake, Brown 201 and its aluminum lake, Purple 201, Red 401 and its aluminum lake,Red 404, Red 405, Red 501, Red 502 and its aluminum lake, Red 503 and its aluminum lake, Red 504 and its aluminum lake, Red 505, Red 506 and its aluminum lake, Orange 401, Orange 402 and its aluminum lake, or Barium Lake, Orange 403, Yellow 401, Yellow 402 and its aluminum lake, Yellow 403(1) and its aluminum lake, Yellow 404, Yellow 405 , Yellow No. 406 and its aluminum lake, Yellow No. 407 and its aluminum lake, Green No. 401, Green No. 402 and its aluminum lake, or barium lake, Blue No. 403, Blue No. 404, Purple No. 401 and its aluminum lake, Black No. 401 and its aluminum lake, chlorophyll, chlorophyllin, malachite green, crystal violet, brilliant green, cobalt phthalocyanine, carotene, vitamin B12, and derivatives derived therefrom. These colorants can be used alone or in combination of two or more.

[0049] The content of the colorant is not particularly limited, but is preferably 0.001 to 5% by mass relative to the total amount of the composition.

[0050] 2. Method for producing the composition The composition can be produced via a step of mixing the (meth)acrylate polymer (A) and the contrast agent (B).

[0051] In the above step, the contrast agent (B) is mixed under conditions such that the major axis of the aggregates in the resulting composition falls within the above range. Specifically, the (meth)acrylate polymer (A) and the contrast agent (B) are preferably mixed in a ratio of (A):(B)=1:0.003 to 1:1.8 (mass ratio) as described above.

[0052] The mixing method is not particularly limited, and includes mixing methods using a Henschel mixer, V blender, ribbon blender, super mixer, double cone mixer, and tumbler blender. Among them, mixing methods using a mixer equipped with stirring blades are preferred, and a Henschel mixer is more preferred. The stirring blade may be provided in one stage, or in multiple stages such as a two-stage configuration of upper and lower blades, or a three-stage configuration of upper, middle, and lower blades, and is not particularly limited.

[0053] According to the study by the present inventors, it has become clear that it is effective to appropriately lower the tip blade speed and the rotation speed of the stirring blade in order to make the major axis of the aggregate of the contrast agent (B) less than 1 mm. That is, while the higher the stirring blade speed and the rotation speed, the easier it is to disperse the material, in this embodiment, it has been found that the stirring blade speed and the rotation speed are not made too high, which makes it more difficult for the material to aggregate.

[0054] The reason for this is believed to be that when the stirring blade speed or rotation speed is increased, not only are the particles of the (meth)acrylate polymer (A) and / or the aggregates of the contrast agent (B) mixed and / or dispersed with disintegration, but also the volume average particle size, shape, crystal structure, surface condition, etc. of these primary particles are changed, thereby increasing the surface activity, and the particles of the (meth)acrylate polymer (A) and / or the particles of the contrast agent (B) re-aggregate with each other.

[0055] Here, disintegration refers to mixing and / or dispersion without affecting the volume average particle size, shape, crystal structure, surface condition, etc. of the primary particles and while maintaining the particle properties.

[0056] For example, the tip blade speed of the stirring blade is preferably 5 to 30.0 m / s. When the tip blade speed is 5 m / s or more, the (meth)acrylate polymer (A) and the contrast agent (B) can be more uniformly dispersed. When the tip blade speed is 30 m / s or less, the aggregation and / or re-aggregation of the contrast agent (B) can be reduced. From the same viewpoint, the tip blade speed of the stirring blade is more preferably 7 to 29.0 m / s, and particularly preferably 7 to 22.0 m / s. The tip blade speed of the stirring blade is calculated as (stirring blade diameter (m) × rotation speed (rpm) × π / 60 (s)). When two or three stirring blades are provided, the diameter of the largest diameter of the stirring blades is adopted as the diameter of the stirring blade.

[0057] The rotation speed of the stirring blade is preferably 50 to 3700 rpm. When the rotation speed is 50 rpm or more, the (meth)acrylate polymer (A) and the contrast agent (B) can be dispersed more uniformly. When the rotation speed is 3700 rpm or less, aggregation and / or reagglomeration of the contrast agent (B) can be reduced. From the same viewpoint, the rotation speed of the stirring blade is more preferably 250 to 2000 rpm, and particularly preferably 500 to 1500 rpm.

[0058] The temperature and time during the mixing may be any conditions that allow the (meth)acrylate polymer (A) and the contrast agent (B) to be mixed uniformly and that allow the major axis of the aggregates of the contrast agent (B) to satisfy the above range. The mixing temperature may be, for example, 20 to 25° C. The mixing time (stirring time) may be, for example, 5 to 60 minutes, or 15 to 30 minutes.

[0059] 3. Hard tissue repair composition The hard tissue repair composition according to one embodiment of the present invention comprises the above composition, a (meth)acrylate monomer (C), and a polymerization initiator (D), and may further comprise antibacterial particles (Z) and / or an inorganic filler and / or a colorant. In the present specification, the hard tissue repair composition is used for bonding hard tissues together, filling hard tissues, bonding hard tissues to artificial objects such as titanium, ceramics, and stainless steel, and bonding hard tissues to other tissues such as soft tissues, but does not include bonding between teeth and fillings (i.e., dental applications). The hard tissue repair composition is preferably used for bone repair applications.

[0060] 3-1. Composition (Dust Composition) The content of the composition is not particularly limited, but is preferably 55 to 81% by mass relative to the total amount of the hard tissue repair composition. When the content of the composition is 55% by mass or more, the content of the (meth)acrylate monomer (C) in the hard tissue repair composition is appropriately reduced, so that the generation of polymerization heat during use and the volumetric shrinkage of the hard tissue repair composition accompanying hardening can be further reduced. When the content of the composition is 81% by mass or less, the content of the (meth)acrylate monomer (C) in the hard tissue repair composition is higher, so that the operability can be further improved and the contrast can be enhanced. Moreover, if the operability is improved, a hard tissue repair composition with excellent homogeneity can be easily obtained, and as a result, various properties such as the compressive strength of the cured body tend to be improved. From the same viewpoint, the content of the composition is more preferably 66 to 74% by mass relative to the total amount of the hard tissue repair composition.

[0061] 3-2. (Meth)acrylate monomers (C) The (meth)acrylate monomer (C) is relatively less irritating to the human body and is suitable as a monomer for the composition for hard tissue repair. The (meth)acrylate monomer (C) may be monofunctional or polyfunctional.

[0062] Examples of monofunctional (meth)acrylate monomers include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and isobornyl (meth)acrylate; 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and the like. hydroxyalkyl esters of (meth)acrylic acid such as 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 1,2-dihydroxypropyl mono(meth)acrylate, 1,3-dihydroxypropyl mono(meth)acrylate, and erythritol mono(meth)acrylate; diethylene glycol mono(meth)acrylate, triethylene glycol mono(meth)acrylate, and polyethylene polyalkylene glycol mono(meth)acrylates such as glycol mono(meth)acrylate and polypropylene glycol mono(meth)acrylate; (poly)alkylene glycol monoalkyl ether (meth)acrylates such as ethylene glycol monomethyl ether (meth)acrylate, ethylene glycol monoethyl ether (meth)acrylate, diethylene glycol monomethyl ether (meth)acrylate, triethylene glycol monomethyl ether (meth)acrylate, polyethylene glycol monomethyl ether (meth)acrylate, and polypropylene glycol monoalkyl ether (meth)acrylate; fluoroalkyl esters of (meth)acrylic acid such as perfluorooctyl (meth)acrylate and hexafluorobutyl (meth)acrylate; silane compounds having a (meth)acryloxyalkyl group such as γ-(meth)acryloxypropyltrimethoxysilane and γ-(meth)acryloxypropyltri(trimethylsiloxy)silane; and (meth)acrylates having a heterocycle such as tetrahydrofurfuryl (meth)acrylate.

[0063] Examples of polyfunctional (meth)acrylate monomers include poly(meth)acrylates of alkane polyols such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, hexylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and polyethylene Examples of the polyoxyalkane polyol poly(meth)acrylate include polyoxyalkane polyol poly(meth)acrylates such as glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, dibutylene glycol di(meth)acrylate, and dipentaerythritol hexa(meth)acrylate; alicyclic or aromatic di(meth)acrylates represented by the following general formula (1); alicyclic or aromatic epoxy di(meth)acrylates represented by the following general formula (2); and polyfunctional (meth)acrylates having a urethane bond in the molecule represented by the following formula (3). [ka] In formula (1), R is a hydrogen atom or a methyl group, m and n are each independently a number from 0 to 10, and R 1 is one of the following formulas: [ka] [ka] (In formula (2), R, n and R 1 R, n and R in the formula (1) 1 (This is the same as [ka] (In formula (3), R is the same as R in formula (1), 2 is any group represented by the following formula: [ka]

[0064] Among these exemplary compounds, Preferred examples of the monofunctional (meth)acrylate monomer include alkyl (meth)acrylates such as methyl (meth)acrylate and ethyl (meth)acrylate; hydroxyalkyl esters of (meth)acrylic acid such as 2-hydroxyethyl (meth)acrylate, 1,3-dihydroxypropyl mono(meth)acrylate and erythritol mono(meth)acrylate; and polyethylene glycol mono(meth)acrylates such as triethylene glycol monomethyl ether (meth)acrylate and triethylene glycol mono(meth)acrylate. As the polyfunctional (meth)acrylate monomer, a di(meth)acrylate having an ethylene glycol chain in the molecule, such as triethylene glycol di(meth)acrylate or polyethylene glycol di(meth)acrylate; a compound represented by the following formula (1)-a, a compound represented by the following formula (2)-a, or a compound represented by the following formula (3)-a is preferred. [ka] (In formula (1)-a, R, m, and n are the same as R, m, and n in formula (1) above.) [ka] (In formula (2)-a, R is the same as R in formula (1) above); [ka] (In formula (3)-a, R is the same as R in formula (1) above.)

[0065] The hard tissue repair composition may contain one type of (meth)acrylate monomer (C) or may contain two or more types of (meth)acrylate monomers (C).

[0066] For example, since (meth)acrylate monomers having an acidic group have excellent adhesion to hard tissues, the above-mentioned (meth)acrylate monomers having no acidic group and (meth)acrylate monomers having an acidic group may be used in combination.

[0067] Examples of (meth)acrylate monomers having an acidic group include (meth)acrylic acid and its anhydride, 1,4-di(meth)acryloxyethylpyromellitic acid, 6-(meth)acryloxyethylnaphthalene-1,2,6-tricarboxylic acid, N-(meth)acryloyl-p-aminobenzoic acid, N-(meth)acryloyl-o-aminobenzoic acid, N-(meth)acryloyl-m-aminobenzoic acid, N-(meth)acryloyl-5-aminosalicylic acid, N-(meth)acryloyl-4-aminosalicylic acid, 4-(meth)acryloxyethyltrimellitic acid and its anhydride, 4-(meth)acryloxybutyltrimellitic acid and its anhydride, 4-(meth)acryloxyhexyltrimellitic acid and its anhydride, 4-(meth)acryloxydecyltrimellitic acid and its anhydride, 2-(meth)acryloyloxy Examples of the monomer include monomers having a carboxylic acid group or an anhydride group thereof, such as benzoic acid, 3-(meth)acryloyloxybenzoic acid, 4-(meth)acryloyloxybenzoic acid, β-(meth)acryloyloxyethyl hydrogen succinate, β-(meth)acryloyloxyethyl hydrogen maleate, β-(meth)acryloyloxyethyl hydrogen phthalate, 11-(meth)acryloyloxy-1,1-undecanedicarboxylic acid, and p-vinylbenzoic acid; monomers having a phosphoric acid group, such as (2-(meth)acryloxyethyl)phosphoric acid, (2-(meth)acryloxyethylphenyl)phosphoric acid, and 10-(meth)acryloxydecyl phosphoric acid; and monomers having a sulfonic acid group, such as p-styrenesulfonic acid and 2-acrylamido-2-methylpropanesulfonic acid. Among them, 4-methacryloxyethyltrimellitic acid and its anhydride are preferable from the viewpoint of further improving the adhesion and / or adhesive strength between the hard tissue repair composition and the adherend. These monomers having an acidic group can also be used as calcium salts.

[0068] The content of the (meth)acrylate monomer (C) is preferably 19 to 59 parts by mass relative to 100 parts by mass of the total of the (A), (C) and (D) components. When the content is 19 parts by mass or more, the operability of the hard tissue repair composition during preparation (during curing) can be further improved. Moreover, if the operability is improved, a hard tissue repair composition with excellent homogeneity can be easily obtained, and as a result, the operability of application and / or filling can be further facilitated, and properties such as penetration into hard tissue can be further improved. When the content is 59 parts by mass or less, the mechanical properties such as compressive strength of the hard tissue repair composition after curing can be improved, and the volumetric shrinkage of the hard tissue repair composition accompanying curing can be further reduced. From the same viewpoint, the content of the (meth)acrylate monomer (C) is more preferably 22 to 54 parts by mass, and even more preferably 29 to 47 parts by mass.

[0069] When the hard tissue repair composition contains a (meth)acrylate monomer having an acidic group, the amount of the (meth)acrylate monomer having an acidic group is preferably 0.005 to 30 parts by mass, more preferably 0.01 to 25 parts by mass, per 100 parts by mass of the (meth)acrylate monomer (C) in total.

[0070] 3-3. Polymerization initiator (D) The polymerization initiator (D) is not particularly limited as long as it can polymerize the (meth)acrylate monomer (C). Among them, organic peroxides and organic boron compounds are preferred, and organic boron compounds are more preferred.

[0071] (organic peroxide) Examples of organic peroxides include diacyl peroxides such as diacetyl peroxide, diisobutyl peroxide, didecanoyl peroxide, benzoyl peroxide (BPO), and succinic acid peroxide; peroxydicarbonates such as diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, and diallyl peroxydicarbonate; peroxyesters such as tert-butyl peroxyisobutyrate, tert-butyl neodecane, and cumene peroxyneodecanate; and peroxysulfonates such as acetylcyclohexylsulfonyl peroxide.

[0072] Organic peroxides may be used as redox initiators in combination with tertiary amines, or in combination with sulfinic acids or their alkali metal salts and a tertiary amine.

[0073] For example, benzoyl peroxide (BPO) may be used in combination with a tertiary amine such as N,N-dimethyl-p-toluidine or N,N-dihydroxyethyl-p-toluidine. By using a tertiary amine, radical species are generated by electron transfer even at room temperature, so that the polymerization reaction can be easily initiated without heating. It is preferable that the tertiary amine is added to the (meth)acrylate monomer (C) in advance.

[0074] (Organoboron Compounds) Examples of organoboron compounds include trialkylborons, alkoxyalkylborons, dialkylboranes, partially oxidized trialkylborons, and alkylborane-amine complexes.

[0075] Examples of trialkylboron include trialkylboron having an alkyl group having a carbon number of 2 to 8, such as triethylboron, tripropylboron, triisopropylboron, tributylboron, tri-sec-butylboron, triisobutylboron, tripentylboron, trihexylboron, triheptylboron, trioctylboron, tricyclopentylboron, and tricyclohexylboron. The alkyl group contained in the trialkylboron may be any of a linear alkyl group, a branched alkyl group, and a cycloalkyl group, and the three alkyl groups contained in the trialkylboron may be the same or different.

[0076] Examples of alkoxyalkyl boranes include monoalkoxydialkyl boranes such as butoxydibutyl borane, and dialkoxymonoalkyl boranes. The alkyl group contained in the alkoxyalkyl borane and the alkyl portion of the alkoxy group may be the same or different.

[0077] Examples of dialkylboranes include dicyclohexylborane and diisoamylborane. The two alkyl groups in the dialkylborane may be the same or different. The two alkyl groups in the dialkylborane may be bonded to form a monocyclic or bicyclic structure. An example of such a compound is 9-borabicyclo[3.3.1]nonane.

[0078] Partially oxidized trialkylboron is a partial oxide of trialkylboron. Partially oxidized tributylboron is preferred. The amount of oxygen added to 1 mole of trialkylboron is preferably 0.3 to 0.9 moles, more preferably 0.4 to 0.6 moles.

[0079] Examples of alkylborane-amine complexes include triethylborane-diaminopropane (TEB-DAP), triethylborane-diethylenetriamine (TEB-DETA), tri-n-butylborane-3-methoxypropylamine (TnBB-MOPA), tri-n-butylborane-diaminopropane (TnBB-DAP), tri-sec-butylborane-diaminopropane (TsBB-DAP), methylaminoethoxydiethylborane (MAEDEB), methylaminoethoxydicyclohexylborane (MAEDCB), and derivatives derived from these.

[0080] When an alkylborane-amine complex is used as the polymerization initiator (D), it is preferable to further use a decomplexing agent together with the (meth)acrylate monomer (C). In this specification, the term "decomplexing agent" refers to a compound that can liberate an alkylborane from an alkylborane-amine complex, and the liberation of the alkylborane enables the initiation of a polymerization reaction.

[0081] As the decomplexing agent, an acid or a (meth)acrylate monomer having the above-mentioned acidic group can be used. Examples of the acid include Lewis acids (e.g., SnCl4, TiCl4), and Bronsted acids (e.g., carboxylic acids, HCl, H2SO4, H3PO4, phosphonic acid, phosphinic acid, and silicic acid).

[0082] Examples of carboxylic acids include those represented by the general formula R-COOH. In the formula, R represents a hydrogen atom, an alkyl group having 1 to 8 carbon atoms, an alkenyl group having 2 to 8 carbon atoms, an alkynyl group having 2 to 8 carbon atoms, or an aryl group having 6 to 10 carbon atoms. The aryl group may be substituted with a substituent such as an alkyl group, an alkoxy group, or a halogen atom. Examples of carboxylic acids represented by the above general formula include acrylic acid, methacrylic acid, acetic acid, benzoic acid, and p-methoxybenzoic acid. Examples of (meth)acrylate-based esters having an acidic group include 4-methacryloxyethyltrimellitic acid and its anhydride.

[0083] Among these organic boron compounds, tributyl boron or partially oxidized tributyl boron is preferred, and partially oxidized tributyl boron is more preferred. When tributyl boron or partially oxidized tributyl boron is used as the organic boron compound, not only is the operability improved, but the composition has an appropriate reactivity with a living body having moisture. When tributyl boron or partially oxidized tributyl boron is used as the organic boron compound, the reaction starts and proceeds even in a place with a lot of moisture, such as a living body, so that monomers are unlikely to remain at the interface between the composition and the living body, and therefore the harm to the living body is extremely small. These organic boron compounds can be used alone or in combination of two or more kinds.

[0084] (solvent) The organic boron compound may be used in combination with an aprotic solvent or alcohol. When the organic boron compound is diluted with these solvents, the heat generation of the flammable organic boron compound becomes milder, the flammability is suppressed, and handling during transportation, storage, and mixing becomes easier. In addition, since sudden heat generation can be suppressed, even when an extremely large amount of the hard tissue repair composition is used, the harm to the tissue in contact with the hard tissue repair composition can be reduced.

[0085] The boiling point of the aprotic solvent at 1 atmospheric pressure is usually 30 to 150° C., and preferably 50 to 120° C. If the boiling point is equal to or higher than the lower limit, the volatilization or scattering of the aprotic solvent during transportation or storage can be further suppressed, and the ignition of the organoboron compound can be further suppressed. If the boiling point is equal to or lower than the upper limit, the amount of the aprotic solvent remaining in the cured product can be further reduced, and the deterioration of physical properties can be further suppressed.

[0086] As the aprotic solvent, a solvent that does not have a group containing active hydrogen such as a hydroxyl group or a mercapto group that reacts with the organic boron compound and can form a homogeneous solution with the organic boron compound is preferred. Examples of the aprotic solvent include hydrocarbons such as pentane, hexane, cyclohexane, heptane, benzene, and toluene; halogenated hydrocarbons such as fluorobenzene, 1,1-dichloroethane, 1,2-dichloroethane, and so-called fluorocarbons; ethers such as diethyl ether, diisopropyl ether, ethylene glycol dimethyl ether, and tetrahydrofuran; ketones such as acetone, methyl ethyl ketone, and diethyl ketone; and esters such as methyl acetate, ethyl acetate, and isopropyl acetate. Among these, saturated aliphatic hydrocarbons such as pentane, hexane, and heptane, ethers, and esters are preferred, and hexane, diisopropyl ether, and ethyl acetate are more preferred.

[0087] The content of the aprotic solvent is preferably 30 to 80 parts by mass relative to 100 parts by mass of the organic boron compound. When the content of the aprotic solvent is 30 parts by mass or more, the dilution effect is enhanced and the effect of suppressing heat generation or ignition is more sufficient. On the other hand, when the content of the aprotic solvent is 80 parts by mass or less, the decrease in the polymerization initiation ability of the polymerization initiator (D) can be suppressed.

[0088] The organic boron compound may contain alcohol in addition to the aprotic solvent or instead of the aprotic solvent. By adding alcohol to the organic boron compound, the reaction by the organic boron compound becomes milder without reducing the polymerization activity, and scorching and ignition can be suppressed even when the composition contacts paper in air. In addition, the property change of the hard tissue repair composition can be suppressed more, so that the operation time for applying and filling the affected area can be secured longer.

[0089] The boiling point of the alcohol at 1 atmospheric pressure is usually 60° C. to 180° C., and preferably 60° C. to 120° C. Examples of the alcohol include methanol, ethanol, n-propanol, n-butanol, n-pentanol, n-hexanol, and n-heptanol. Among them, alcohols having 4 or less carbon atoms, i.e., methanol, ethanol, n-propanol, and n-butanol, are preferred, and ethanol and n-propanol are more preferred.

[0090] The content of the alcohol is usually 0.01 to 40 parts by mass, preferably 0.1 to 30 parts by mass, and more preferably 0.5 to 20 parts by mass, based on 100 parts by mass of the organoboron compound. When the content of the alcohol is 0.01 parts by mass or more, the dilution effect is enhanced and the effect of suppressing heat generation or ignition is more sufficient. On the other hand, when the content of the alcohol is 40 parts by mass or less, the decrease in the polymerization initiation ability of the polymerization initiator (D) can be reduced.

[0091] The content of the polymerization initiator (D) is preferably 0.1 to 10 parts by mass, more preferably 1.0 to 7.0 parts by mass, and particularly preferably 2.1 to 4.3 parts by mass, based on 100 parts by mass of the total of the (A), (C) and (D) components. When the content of the polymerization initiator (D) is equal to or greater than the lower limit, the polymerization is likely to proceed in a shorter time, and the start of the usable time of the hard tissue repair composition immediately after preparation (during curing) can be accelerated. When the content of the polymerization initiator (D) is equal to or less than the upper limit, the rapid progress of polymerization is more suppressed, and the generation of polymerization heat during use can be reduced.

[0092] 3-4. Manufacturing method of hard tissue repair composition The above-mentioned hard tissue repair composition can be prepared by mixing a (meth)acrylate polymer (A), a contrast agent (B), a (meth)acrylate monomer (C), a polymerization initiator (D), and any other components.

[0093] The mixing order is not particularly limited. However, for example, from the viewpoint of further enhancing the stability of the hard tissue repair composition, it is preferable to first mix the (meth)acrylate monomer (C) and the polymerization initiator (D), and then mix the mixture with a composition containing the (meth)acrylate polymer (A) and the contrast agent (B).

[0094] 3-5.Applications The above-mentioned hard tissue repair composition is applied to and / or filled into an affected area, and then hardened by a polymerization reaction to become a hardened material.

[0095] Before hardening, the composition may be sterilized by treatment with dry heat, steam, ethylene oxide (EO), hydrogen peroxide or other gas, filtration, liquid, etc. In addition, before filling the affected area with the composition for hard tissue repair, the surface of the affected area may be disinfected with a disinfectant such as alcohol. Furthermore, before filling the affected area with the composition for hard tissue repair, pretreatment may be performed for the purpose of improving adhesion to the affected area. Examples of the pretreatment liquid include physiological saline.

[0096] 4. Hard tissue repair kit In the case where the form or performance of the hard tissue repair composition changes during storage, the hard tissue repair composition may be stored as a hard tissue repair kit having a member in which each component contained in the hard tissue repair composition is divided into two or more, preferably three or more, in any combination. Then, before use, these components may be mixed to prepare a hard tissue repair composition.

[0097] As a method for storing the above components, it is preferable to store them by dividing them into three compositions: a composition containing the (meth)acrylate polymer (A) and the contrast agent (B), a composition containing the (meth)acrylate monomer (C), and a composition containing the polymerization initiator (D).

[0098] Alternatively, the mixture may be divided into two compositions: a first composition containing one of the (meth)acrylate monomer (C) and the polymerization initiator (D) and the composition containing the meth)acrylate polymer (A) and the contrast agent (B), and a second composition containing the other of the (meth)acrylate monomer (C) and the polymerization initiator (D). For example, the mixture may be divided into two compositions: a first composition containing the composition containing the (meth)acrylate polymer (A) and the contrast agent (B) and the (meth)acrylate monomer (C), and a second composition containing the polymerization initiator (D).

[0099] As a member for storing the (meth)acrylate monomer (C) and the polymerization initiator (D), for example, a sealable resin container or glass ampoule having gas barrier properties can be used from the viewpoint of further suppressing the volatilization and scattering of these components. As a member for storing the (meth)acrylate polymer (A), there can be mentioned a resin or glass container with good sealability for preventing moisture absorption and / or for performing radiation sterilization such as electron beam or gamma ray, and a container or bag made of a resin nonwoven fabric or sterilized paper for performing sterilization with a gas such as ethylene oxide (EO) or hydrogen peroxide.

[0100] In the case of a hard tissue repair kit divided into three parts, a composition containing a (meth)acrylate polymer (A) and a contrast agent (B), a composition containing a (meth)acrylate monomer (C), and a composition containing a polymerization initiator (D), it is preferable to 1) mix the (meth)acrylate monomer (C) and the polymerization initiator (D), and then 2) mix the resulting mixture with the composition containing the (meth)acrylate polymer (A) and the contrast agent (B). This makes it possible to obtain a hard tissue repair composition with more stable performance.

[0101] An example of a hard tissue repair kit is a kit having components in which the above-mentioned components are stored in three or more portions, and components for removing and mixing each component from these components (e.g., an orthopedic cement mixer, an orthopedic cement injector, an orthopedic cement dispenser, a cement gun, a mixing container, a mixing dish, a cylinder, etc.).

[0102] As a hard tissue repair kit, for example, a composition containing a (meth)acrylate polymer (A) and a contrast agent (B), a (meth)acrylate monomer (C), and a polymerization initiator (D) may be separately stored in three or more chambers separated by a partition or spacer in one mixing container. An example of the kit has a stirring unit that allows the (meth)acrylate monomer (C) and the polymerization initiator (D) to pass through a bypass designed in advance in the mixing container by breaking or moving the partition or removing the spacer, come into contact with the composition containing the (meth)acrylate polymer (A) and the contrast agent (B), and mix by operating the stirring blade installed.

[0103] A kit consisting of one mixing container in which each component is stored in three or more separated chambers can reduce complexity compared to a method in which the components are divided into two or more components, typically individual containers, and then mixed immediately before use. Furthermore, a kit can be directly applied to the affected area using a tool such as a cement gun that can inject the composition directly from the mixing container, making it technically and economically useful.

[0104] Examples of tools for filling the affected area include an orthopedic cement mixer, an orthopedic cement injector, an orthopedic cement dispenser, and a cement gun.

[0105] The above-mentioned hard tissue repair kit may contain a disinfectant such as the above-mentioned alcohol, a solution for pretreatment for the purpose of improving adhesion, etc.

[0106] Furthermore, when storing in the above-mentioned kit or the like, sterilization may be performed using electromagnetic waves such as visible light, preferably under conditions that do not cause deterioration of the components (for example, the monomer does not harden). EXAMPLES

[0107] 1. Measurement of physical properties (1) Weight average molecular weight (Mw) The (meth)acrylate polymer was dissolved in reagent grade tetrahydrofuran (manufactured by Wako Pure Chemical Industries, Ltd.), and the solution was filtered through a hydrophobic 0.45 μm polytetrafluoroethylene filter. The filtered solution was used as a sample, and the weight average molecular weight (Mw) of the (meth)acrylate polymer was measured in terms of standard polystyrene using high performance liquid chromatography (manufactured by Shimadzu Corporation, LC-10AD), a separation column (PLgel (10 μm) MIXED-B × 2), and a detector (manufactured by Shodex Corporation, RI-101).

[0108] (2) Volume average particle size D 50 Reagent-grade methanol (solvent refractive index: 1.33) (manufactured by Wako Pure Chemical Industries, Ltd.) was used as the dispersion solvent, and the (meth)acrylate polymer was dispersed for 5 minutes (output: 25 W) using an ultrasonic homogenizer built into the device. The particle size distribution of this dispersion was measured using a Microtrac MT3300EXII (a particle size distribution analyzer manufactured by Microtrac) at a circulation speed of 50% (65 mL / sec at 100%) under concentration conditions within the appropriate range of the device Loading Index. The volume average particle diameter D of the (meth)acrylate polymer (A) 50 The value of was taken as 50% of the cumulative volume average particle size in the entire (meth)acrylate polymer (A). The contrast agent (B) was also measured in the same manner.

[0109] (3) Specific surface area The specific surface area of ​​the (meth)acrylate polymer was measured by vacuum degassing at room temperature as a pretreatment, and then using a BELSORP-mini (MicrotrackBell) device, at liquid nitrogen temperature, by a nitrogen gas adsorption method.

[0110] 2. Preparation and Evaluation of Compositions 2-1. Preparation of the composition The (meth)acrylate polymer (A) has a weight average molecular weight and a volume average particle diameter D 50 Spherical polymethyl methacrylate (A1) having a specific surface area and amorphous polymethyl methacrylate (A2) were used. When both spherical polymethyl methacrylate (A1) and amorphous polymethyl methacrylate (A2) were contained, the content ratio of the spherical polymethyl methacrylate (A1) to the amorphous polymethyl methacrylate (A2) was (A1):(A2) = 83.3:16.7 (mass ratio). In addition, the contrast agent (B) has a volume average particle diameter D 50 Barium sulfate (BaSO4) (manufactured by Sakai Chemical Industry Co., Ltd.) or zirconium oxide (ZrO2) (manufactured by Tosoh Corporation) having the above structure was used. In addition, gentamicin sulfate (manufactured by Wako Pure Chemical Industries, Ltd., titer = 654 μg / mg) was used as the antibacterial particles (Z).

[0111] In compositions X1 to X5, X7 to X14, X16 to X20, X22 to X27, and X29, the (meth)acrylate polymer (A) and the contrast agent (B) were mixed in the ratios (parts by mass) and mixing conditions shown in Tables 1 to 4 to prepare the compositions. The mixing was performed using a Henschel mixer FM20RC / I type (manufactured by Nippon Coke and Engineering Co., Ltd.). The upper blade was an ST blade, and the lower blade was an AO blade, both of which had a blade length of 0.275 m.

[0112] For compositions X6, X15, X21, and X28, the (meth)acrylate polymer (A), the contrast agent (B), and the antibacterial particles (Z) were mixed in the ratios (parts by mass) shown in Tables 1 to 4 under the same mixing conditions as described above to prepare the compositions.

[0113] In Tables 1 to 4, the content of the (meth)acrylate polymer (A) indicates the total content of the spherical polymethyl methacrylate (A1) and the amorphous polymethyl methacrylate (A2).

[0114] 2-2. Evaluation of the composition The major axis of the contrast agent aggregates in the obtained composition was measured by the following method.

[0115] (Measurement of the longest diameter of contrast agent aggregates) First, the composition was spread on a polyethylene plate in a uniform layer of 2 mm thickness (circular shape with a diameter of φ=10 mm) and photographed with an X-ray fluoroscopy device FLEX-M863 (manufactured by Beam Sense Co., Ltd.) The tube voltage of the X-ray fluoroscopy device was 70 kV, the tube current was 100 μA, the photographing time was 1000 ms, and the number of additions was 3. Next, in the obtained image, the major axis of any five highly X-ray-opaque parts (aggregates of contrast agent (B)) in the measurement region (circular with a diameter of φ=10 mm) was measured by image analysis, and the longest major axis value among these was taken as the major axis of the aggregate.

[0116] The preparation conditions and evaluation results of compositions X1 to X8 are shown in Table 1, the preparation conditions and evaluation results of compositions X9 to X16 are shown in Table 2, the preparation conditions and evaluation results of compositions X17 to X22 are shown in Table 3, and the preparation conditions and evaluation results of compositions X23 to X29 are shown in Table 4.

[0117] [Table 1]

[0118] [Table 2]

[0119] [Table 3]

[0120] [Table 4]

[0121] As shown in Tables 1 to 4, when a composition is prepared using only spherical (meth)acrylate polymer (A1) as component (A), when the content ratio (B) / (A) of component (A) to component (B) is a predetermined value or less and the mixing is performed under conditions of a tip blade speed of 30.0 m / s or less, it can be seen that the major axis of the aggregates of contrast agent (B) in the composition becomes small, less than 1 mm (compare X1 to X5, X7 to X8, X17 to X20, and X22).

[0122] Even when a composition is prepared by combining a spherical (meth)acrylate polymer (A1) and an amorphous (meth)acrylate polymer (A2) as the component (A), when the content ratio (B) / (A) of the component (A) to the component (B) is a predetermined value or less and the mixing is performed under conditions where the tip blade speed is 30.0 m / s or less, it can be seen that the major axis of the aggregates of the contrast agent (B) in the composition becomes small, less than 1 mm (compare X9 to X14, X16, X23 to X27, and X29).

[0123] Even when a composition further containing antibacterial particles (Z) is used, regardless of whether only component (A1) is used as component (A) or whether component (A1) and component (A2) are used in combination, when the content ratio (B) / (A) of component (A) to component (B) is a predetermined value or less and the tip blade speed is mixed at 30.0 m / s or less, it can be seen that the major axis of the aggregates of contrast agent (B) in the composition becomes small, less than 1 mm (comparison of X6, X15 with X21, X28).

[0124] 3. Preparation and evaluation of compositions for hard tissue repair 3-1. Preparation of hard tissue repair composition First, methyl methacrylate ((meth)acrylate monomer (C)) and (polymerization initiator (D)) were placed in a 50 mL glass sample tube in the blending ratios shown in Tables 5 to 8 and premixed.

[0125] As the polymerization initiator (D), a mixture of 85 parts by mass of partially oxidized tributyl boron and 15 parts by mass of ethanol (manufactured by Mitsui Chemicals, Inc., product number BC-S1i) (the total amount of the polymerization initiator (D) being 100 parts by mass) was used.

[0126] Next, the above-prepared compositions shown in Tables 1 to 4 and the mixture of (meth)acrylate monomer (C) and polymerization initiator (D) mixed in advance were placed in the mixing bowl of an orthopedic bone cement mixer (ZimmerBiomet disposable mixing bowl with spatula) in the composition ratios (parts by mass) shown in Tables 5 to 8, and mixed using the attached spatula to prepare a composition for hard tissue repair, which was then cured. The mixing time was 60 seconds.

[0127] The prepared hard tissue repair composition was hardened using a mold having a shape and made of a material specified in the international standard for bone cement, ISO5833:2002 (surgical implants - acrylic resin cement), which will be described later.

[0128] 3-2. Evaluation of compositions for hard tissue repair The compressive strength of the hardened body of the obtained hard tissue repair composition was measured by the following method.

[0129] (Compressive strength measurement) The compressive strength of the hardened body of the obtained composition for hard tissue repair was measured under the conditions specified in the international standard ISO5833:2002 (surgical implants - acrylic resin cement) for bone cement.

[0130] The preparation conditions and evaluation results of hard tissue repair compositions Y1 to Y8 are shown in Table 5, the preparation conditions and evaluation results of hard tissue repair compositions Y9 to Y16 are shown in Table 6, the preparation conditions and evaluation results of hard tissue repair compositions Y17 to Y22 are shown in Table 7, and the preparation conditions and evaluation results of hard tissue repair compositions Y23 to Y29 are shown in Table 8.

[0131] [Table 5]

[0132] [Table 6]

[0133] [Table 7]

[0134] [Table 8]

[0135] As shown in Tables 3 to 4 and Tables 7 to 8, the compressive strength of the hardened bodies of hard tissue repair compositions Y17 to Y29, which use compositions in which the major axis of the aggregates of the contrast agent (B) exceeds 1 mm, is lower than 70 MPa.

[0136] In contrast, as shown in Tables 1-2 and Tables 5-6, the compressive strength of the hardened bodies of hard tissue repair compositions Y1-Y16, which use compositions in which the major axis of the contrast agent (B) aggregates is less than 1 mm, is higher than 70 MPa.

[0137] From these, it can be seen that by using a composition in which the major axis of the contrast agent (B) aggregates is less than 1 mm, the decrease in compressive strength of the hardened body is reduced and good strength can be obtained. [Industrial Applicability]

[0138] According to the present invention, it is possible to provide a composition that can provide a hardened body of a composition for hard tissue repair that has contrast properties and sufficient and appropriate compressive strength.

[0139] The composition for hard tissue repair of the present invention is useful as a bone cement used for, for example, adhering and / or joining hard tissues together, filling the interior of hard tissues, adhering and / or bonding hard tissues to artificial objects such as titanium, ceramics, stainless steel, etc., adhering and / or bonding hard tissues to other tissues such as soft tissues, and fixing hard tissues such as bone and cartilage to artificial joints, as a filler for bone defects, a bone filling material, a bone fixing material, and an artificial bone.

[0140] Furthermore, the present invention is useful for vertebral cages and vertebral fixation spacers used for filling the gap between upper and lower vertebral bodies in interbody fixation surgery in the treatment of degenerative diseases and injuries of the thoracic or lumbar vertebrae, such as herniated disc, spinal canal stenosis, and spinal compression fractures.

[0141] Furthermore, when the composition of the present invention contains antibacterial particles (Z), the prepared hard tissue repair composition is also useful as a molding material for medical cement spacers and cement beads. For example, if an infection occurs at the affected area after an artificial joint operation, the inserted artificial joint may be removed. In order to fill the gap caused by this removal, a cement spacer containing an antibiotic is usually used. In some cases, the artificial joint is not removed, but only debridement (removal and cleaning of necrotic tissue) is performed, and antibacterial cement beads are embedded. Furthermore, there are also reports of the use of a bendable spacer. For example, a cement spacer or cement bead having a desired shape can be obtained by hardening the hard tissue repair composition of the present invention in a mold.

Claims

1. A composition comprising a (meth)acrylate polymer (A) and a contrast agent (B), The major axis of the aggregate of the contrast agent (B) in the composition is less than 1.0 mm. composition.

2. The contrast agent (B) contains barium sulfate or zirconium oxide; The composition of claim 1.

3. The content ratio of the (meth)acrylate polymer (A) to the contrast agent (B) is (A):(B)=1:0.003 to 1:1.8 (mass ratio). The composition of claim 1.

4. The content of the (meth)acrylate polymer (A) is 33 to 99.8% by mass based on the total amount of the composition. The composition of claim 1.

5. The content of the contrast agent (B) is 0.1 to 65% by mass based on the total amount of the composition. The composition of claim 1.

6. The volume average particle size of the contrast agent (B) is 5.0 μm or less. The composition of claim 1.

7. Further comprising antibacterial particles (Z), The composition of claim 1.

8. The content of the antibacterial particles (Z) is 0.1 to 20% by mass based on the total amount of the composition. The composition of claim 7.

9. The composition according to any one of claims 1 to 8, a (meth)acrylate monomer (C), and a polymerization initiator (D), Hard tissue repair composition.

10. Used to repair bones, The composition for hard tissue repair according to claim 9 .

11. A composition according to any one of claims 1 to 8, A composition comprising a (meth)acrylate monomer (C); A composition comprising a polymerization initiator (D); The device has a member housed in a divided manner. Hard tissue repair kit.

12. A first composition comprising one of a (meth)acrylate monomer (C) and a polymerization initiator (D) and the composition according to any one of claims 1 to 8; a second composition containing the other of the (meth)acrylate monomer (C) and the polymerization initiator (D); The device has a member housed in a divided manner. Hard tissue repair kit.

13. 1. A method for producing a composition, comprising: The method includes a step of mixing the (meth)acrylate polymer (A) and the contrast agent (B) by stirring in a mixer equipped with a stirring blade, In the process, The (meth)acrylate polymer (A) and the contrast agent (B) are mixed in a ratio of (A):(B)=1:0.003 to 1:1.8 (mass ratio), Mixing is performed under the condition that the tip blade speed of the stirring blade is 5 to 30.0 m / s. Method for producing the composition.

14. The contrast agent (B) contains barium sulfate or zirconium oxide; A method for producing the composition of claim 13.

15. The volume average particle size of the contrast agent (B) is 5.0 μm or less. A method for producing the composition according to claim 13 or 14.

16. Further comprising antibacterial particles (Z), A method for producing the composition according to claim 13 or 14.

Citation Information

Patent Citations

  • Hard tissue repair composition and hard tissue repair kit

    WO2019181477A1